Genome-Wide Transcriptional Response of Saccharomyces cerevisiae to Stress-Induced Perturbations - Taymaz-Nikerel, Hilal; Cankorur-Cetinkaya, Ayca; Kirdar, Betul (Frontiers in Bioengineering and Biotechnology, 2016)
Cells respond to environmental and/or genetic perturbations in order to survive and proliferate. Characterization of the changes after various stimuli at different -omics levels is crucial to comprehend the adaptation of cells to changing conditions. Genome wide quantification and analysis of transcript levels, the genes affected by perturbations, extends our understanding of cellular metabolism by pointing out the mechanisms that play role in sensing the stress caused by those perturbations and related signaling pathways, and in this way guides us to achieve endeavors such as rational engineering of cells or interpretation of disease mechanisms. Saccharomyces cerevisiae as a model system has been studied in response to different perturbations and corresponding transcriptional profiles were followed either statically or/and dynamically, short- and long- term. This review focuses on response of yeast cells to diverse stress inducing perturbations including nutritional changes, ionic stress, salt stress, oxidative stress, osmotic shock, as well as to genetic interventions such as deletion and over-expression of genes. It is aimed to conclude on common regulatory phenomena that allow yeast to organize its transcriptomic response after any perturbation under different external conditions.